Rupture of the Left External Iliac Artery and Right Groin Pseudoaneurysm Formation following Angioplasty in a Patient with Neurofibromatosis Type 1 and Undiagnosed Bilateral Phaeochromocytoma. (25th July 2013) - Doleman, Brett; Kaushal, Sushila; Patel, Asha; Kirk, James; Quarmby, John
Abstract : Neurofibromatosis type 1 (NF1) is a genetic condition, which affects 1 in every 3000 births. Patients with NF1 are at increased risk of a variety of vascular abnormalities. This report presents the case of a 60-year-old male with NF1 who suffered a left external iliac rupture and a right pseudoaneurysm following angioplasty. In addition, these were further complicated by previously undiagnosed, bilateral phaeochromocytomas. The inherent weakness in vessel wall architecture found in NF1 coupled with the hypertension evident during and after the procedure contributed to haemorrhage and pseudoaneurysm formation. Caution must be taken in such patients when considering vascular intervention.